2021
DOI: 10.1007/s11031-021-09921-2
|View full text |Cite|
|
Sign up to set email alerts
|

The role of daily need crafting in daily fluctuations in adolescents’ need-based and affective experiences

Abstract: Based on self-determination theory, this diary study examined associations between adolescents' daily need crafting and daily fluctuations in their need-based and affective experiences. We also examined the role of daily perceived autonomysupportive parenting in adolescents' daily need-crafting. Adolescents (N = 159; M age = 15.56; 62% female) filled out a diary for seven consecutive days. Multilevel path analyses indicated that need crafting varied on a day-to-day basis, with daily need crafting relating posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 61 publications
5
27
0
Order By: Relevance
“…According to the literature, both managers and colleagues can support others’ need for autonomy (Jungert et al, 2013 , 2020 ; Kaabomeir et al, 2022 ; Moreau & Mageau, 2012 ). More recent studies have confirmed individuals’ role in supporting their own need for autonomy as well (Laporte et al, 2021 , 2022a , 2022b ; Sheldon et al, 2021 ). Congruent with SDT assumptions, Laporte et al ( 2021 ) introduced the concept of need crafting as a proactive side of need satisfaction.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…According to the literature, both managers and colleagues can support others’ need for autonomy (Jungert et al, 2013 , 2020 ; Kaabomeir et al, 2022 ; Moreau & Mageau, 2012 ). More recent studies have confirmed individuals’ role in supporting their own need for autonomy as well (Laporte et al, 2021 , 2022a , 2022b ; Sheldon et al, 2021 ). Congruent with SDT assumptions, Laporte et al ( 2021 ) introduced the concept of need crafting as a proactive side of need satisfaction.…”
mentioning
confidence: 87%
“…Need-supportive practices are viewed as eudaemonic practices that boost need satisfaction (Martela & Sheldon, 2019 ). Studies support the boosting effect of such practices by reporting that need support (Kaabomeir et al, 2022 ; Sheldon et al, 2021 ) and need crafting (Laporte et al, 2021 ; 2022a , 2022b ) are associated positively with need satisfaction. As a spin-off, need satisfaction boosts well-being (Martela & Sheldon, 2019 ; Laporte et al, 2022a , 2022b ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations